Models of the Market Economy in the Global Economy. Objections and Recommendations to Change the Principles in the Situation of the Global Financial Crisis - Kosztowniak, Aneta (Modele gospodarki rynkowej w gospodarce globalnej. Zarzuty i zalecenia zmian zasad w sytuacji globalnego kryzysu finansowego, 2011)
The financial crisis of 2007 disturbed both the static and the dynamic effectiveness in the global economy, entailed a decline in economic growth, disturbed the structure of domestic production, savings, and induced increased income inequalities, i.e. affected all the five criteria of the market economy-oriented system efficiency as mentioned by B. Balassa. A comparative analysis of market economies indicates that Europe is more vulnerable to critical phenomena and is less efficient economically than the US which is able to stimulate economic growth more rapidly. But, the high external debt and dollar depreciation are quintessential problems for the American economy. If these problems are not being solved, the result will be probably the next phase of the crisis and definitely change for the worse efficiency of the Anglo-Saxon model.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 192, s. 23-32
Keywords: models of the market economy; global financial crisis